PENDEKATAN QSPM SEBAGAI DASAR PERUMUSAN STRATEGI PENINGKATAN PENDAPATAN ASLI DAERAH KABUPATEN BATANG, JAWA TENGAH - Nurhayati, Siti (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2008)
The aim of this research is to analyse of increasing Local Original Income (LOI) strategy and his influence to increasing the regional income. The research was done at Local Government Income of Batang regency. This research also want to know that the LOI strategy was based on the potencies and opportunities. The analyzing use the IFE, EFE, SWOT, and then QSPM to choose strategic formulation; and proportion models. The result of Internal â External analysis show that increasing strategy of LOI have not based on the potencies and opportunities that they have yet. The Local Government Income of Batang Regency needs the intensification strategy for increasing the LOI. By the QSPM analysis, the Local Government Income of Batang Regency needs extensification strategy for LOI acceptance.